2013
DOI: 10.1007/s10029-012-1032-0
|View full text |Cite
|
Sign up to set email alerts
|

Histological findings in direct inguinal hernia

Abstract: Presence of inflammatory infiltration, vascular damage and regressive nerve lesions, as well as fibrohyaline degeneration and fatty dystrophy of the muscle fibers are the features seen within the examined structures surrounding the direct hernia opening. These findings could represent a reason for a structural and functional weakening of the inguinal region. Consequently, the described results lead the authors to depict these changes as a plausible cause of direct inguinal hernia protrusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Following the latest evidence in the pathophysiology of the herniated groin, a new line of thought has recently emerged. A series of scientific reports has revealed that degenerative injury affecting the herniated groin histologically assumes the typical aspect of chronic compressive damage . It is evident that no other source of chronic compression exists in this area except the steady impact of the abdominal viscera against the groin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the latest evidence in the pathophysiology of the herniated groin, a new line of thought has recently emerged. A series of scientific reports has revealed that degenerative injury affecting the herniated groin histologically assumes the typical aspect of chronic compressive damage . It is evident that no other source of chronic compression exists in this area except the steady impact of the abdominal viscera against the groin.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, this feature is thought to be related to the static nature of the flat meshes which, incorporated by motionless and rigid tissue elements, impede the regular muscle function of the repaired groin . Furthermore, recent studies concerning the pathogenesis of hernia disease have demonstrated the degenerative source of inguinal protrusions . This has generated new interest in the search for a more physiological and pathogenetic consequent repair concept of inguinal hernias.…”
mentioning
confidence: 99%
“…Previous studies in mice suggest that the development of scrotal hernias may be associated with abnormalities in the abdominal muscles, particularly those in the inguinal region ( 9 , 10 ). In men, histological studies have identified myocyte (myofiber) atrophy, fibrosis, and fatty degeneration in the internal inguinal ring area from indirect hernia patients and in the abdominal wall surrounding a direct hernia border ( 11 13 ). LAM tissue is composed of layers of oblique and transverse skeletal muscle made of myocytes.…”
mentioning
confidence: 99%
“…As the inguinal region is one of the most motile areas of the body, it is surprising that all prosthetics used for hernia repair are static devices. Recent evidence indicates that inguinal hernia is a degenerative disease . Therefore, to repair abdominal wall defects, the goal of the employed therapy should be to regenerate typical abdominal wall tissue components.…”
mentioning
confidence: 99%